Research on the Anxiety and Depression of Patients with Mechanical Ocular Injuries: A Cross-Sectional Study - Li M; Wang Y; Chen H; Zheng F; Su Z; Li J; Yan H (Psychology Research and Behavior Management)
Mengxuan Li,1– 3 Yuhao Wang,4 Hanhui Chen,4 Fang Zheng,5 Zhitao Su,5 Jie Li,4 Hua Yan1– 3 1Department of Ophthalmology, Tianjin Medical University General Hospital, Tianjin, 300052, People’s Republic of China; 2Laboratory of Molecular Ophthalmology, Tianjin Medical University, Tianjin, 300070, People’s Republic of China; 3Key Laboratory of Ocular Trauma, Tianjin, 300070, People’s Republic of China; 4Laboratory of Biological Psychiatry, Institute of Mental Health, Tianjin Anding Hospital, Mental Health Center of Tianjin Medical University, Tianjin, 300222, People’s Republic of China; 5Eye Center, The Second Affiliated Hospital Zhejiang University School of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaCorrespondence: Hua Yan, Department of Ophthalmology, Tianjin Medical University General Hospital, Tianjin, 300052, People’s Republic of China, Fax +86-22-27813550, Email zyyyanhua@tmu.edu.cnPurpose: The present study aimed to investigate the prevalence of anxiety and depression in patients with mechanical ocular injuries, and the effects of worry and resilience on anxiety and depression.Patients and Methods: Patients with one eye of mechanical ocular injuries and healthy residents were recruited from June 8, 2022, to March 1, 2023. All subjects participated in psychologically relevant questionnaires including the Self-rating Anxiety Scale(SAS), the Self-rating Depression Scale(SDS), the Connor- Davidson Resilience Scale (CD-RISC), and the Penn State Worry Questionnaire(PSWQ). Data were collected and subjected to statistical analysis.Results: There were no significant differences in SAS and SDS total scores based on demographics (p> 0.05) except for the subjective appraisal of the family economy (p< 0.05). The SAS and SDS total scores and the positive rates of anxiety and depression in the ocular trauma group were significantly higher than those in the healthy control group (p< 0.01). The positive rates of anxiety and SAS total scores of individuals with mild visual impairment were significantly higher than those with low vision (p< 0.01) and blindness (p< 0.05). There was no difference between the remaining groups. The positive rates of anxiety and SAS total score (36.5%, 45.92) of individuals with mild visual impairment were significantly higher than those with low vision (4.3%, 38.15) (p< 0.01) and blindness (19.4%, 40.19) (p< 0.05). There was no difference between the other groups. All effects of mechanical ocular injuries on anxiety and depression were significant (p< 0.01). The indirect mediating effects on anxiety by worry alone, resilience alone, resilience, and worry were significant (p< 0.01). The mediating indirect impact on depression by worry alone (p< 0.01), worry and resilience (p< 0.05) were significant while resilience (p> 0.05) did not show a significant mediation effect.Conclusion: Patients with mechanical ocular injuries are prone to developing anxiety and depression with resilience and worry playing a mediating role.Keywords: anxiety, depression, resilience, worry